Trabecular organization of the proximal femur in Paranthropus robustus: Implications for the assessment of its hip joint loading conditions. Issue 153 (April 2021) - Cazenave, Marine; Oettlé, Anna; Pickering, Travis Rayne; Heaton, Jason L.; Nakatsukasa, Masato; Francis Thackeray, J.; Hoffman, Jakobus; Macchiarelli, Roberto
Abstract: Reconstruction of the locomotor repertoire of the australopiths ( Australopithecus and Paranthropus ) has progressively integrated information from the mechanosensitive internal structure of the appendicular skeleton. Recent investigations showed that the arrangement of the trabecular network at the femoral head center is biomechanically compatible with the pattern of cortical bone distribution across the neck, both suggesting a full commitment to bipedalism in australopiths, but associated with a slightly altered gait kinematics compared to Homo involving more lateral deviation of the body center of mass over the stance limb. To provide a global picture in Paranthropus robustus of the trabecular architecture of the proximal femur across the head, neck and greater trochanter compartments, we applied techniques of virtual imaging to the variably preserved Early Pleistocene specimens SK 82, SK 97, SK 3121, SKW 19 and SWT1/LB-2 from the cave site of Swartkrans, South Africa. We also assessed the coherence between the structural signals from the center of the head and those from the trabecular network of the inferolateral portion of the head and the inferior margin of the neck, sampling the so-called vertical bundle, which in humans represents the principal compressive system of the joint. Our analyses show a functionally related trabecular organization in Pa. robustus that closely resembles the extant human condition, but which also includes some specificities in local textural arrangement. The network of the inferolateral portion of the head shows a humanlike degree of anisotropy and a bone volume fraction intermediate between the extant human and the African ape patterns. These results suggest slight differences in gait kinematics between Pa. robustus and extant humans. The neck portion of the vertical bundle revealed a less biomechanically sensitive signal. Future investigations on the australopith hip joint loading environment should more carefully investigate the trabecular structure of the trochanteric region and possible structural covariation between cortical bone distribution across the neck and site-specific trabecular properties of the arcuate bundle.